A longitudinal study of migration and health: Empirical evidence from Thailand and its implications - Chalermpol Chamchan; Win Kit Chan; Sureeporn Punpuing (United Nations Research Institute for Social Development (UNRISD), 2014)
Using longitudinal data and analysis from 2005 to 2009, this study aims to examine the complex relationship between rural-urban migration and health in Thailand. Measured by Physical and Mental Component Summary Scales from the Short Form (SF-36) Health Survey, the physical and mental health of respondents was assessed and tracked over this five-year period with regard to migration status and relevant socio-demographic characteristics. A total of 2,397 individuals of prime migration age (between the ages of 15 and 29) in 2005 are included in this analysis. The study finds that rural-urban migration in Thailand depended on the individuals health. The likelihood of migrating from a rural origin to an urban destination was higher for those who had better physical health but poorer mental health. Compared to residents in urban destinations, migrants were, on average, physically and mentally healthier upon arrival, or up to two years after migrating. Their health, nevertheless, deteriorated within two to four years after migration. By using multilevel modelling, migration was found to affect an individuals physical health positively in the short-run, but negatively in the long run. Migration impacts on mental health were similar, but weak, and insignificant when controlled by other factors. Based on empirical findings from Thailand, the applicability of a longitudinal design for migration and health studies in different contexts of developing countries is discussed. China in particular - as the fastest growing economy in the developing world and a country that is currently facing a huge flow of domestic rural-urban migration - is considered in the discussion.
Keywords: 330